Detroit School Reform in Comparative Contexts Community Action Overcoming Policy Barriers - St. John, Edward; Girmay, Feven (Neighborhoods, Communities, and Urban Marginality, 2019)
This book critically examines how the narrative of global economic competition was used to rationalize college preparatory curriculum for all high school students and promote charter schools in Detroit. Using mixed qualitative and quantitative methods, the study identifies neighborhood risk factors undermining students' academic success, along with the positive effects of churches and service centers as mitigating forces. The authors focus on a range of topics and issues including market competition, urban decline, community resources, testing and accountability, smaller schools, and engaged learning. The volume illustrates how action studies by engaged scholars working with community activists empowers students to overcome emerging barriers.